Zonynyms in German, Uzbek and Russian Languages (By the Example of Phraseological Units) - Begasheva Sharofat Nematullaevna (Genius Publishing Group, 2022)
This article analyzes the example of phraseological units of zoonyms in German, Uzbek and Russian.
Keywords: Phraseology; animal world; zoonyms; zoomorphisms